Processing of visual stimuli following infant directed speech: attention-guiding effects of unfamiliar speech - Peykarjou, Stefanie; Wissner, Julia; Pauen, Sabina (Infancy, 2024)
This study investigates attention modulation as a function of infant directed (ID) versus adult directed (AD) speech in seven-month-old infants using electroencephalographic measures. In three experiments, infants were presented with either ID speech or AD speech as stimuli, followed by highly variable images of inanimate objects as targets. In Experiment 1 (N = 18), images were preceded by ID or AD speech with semantic content (“Look here”). Contrary to hypothesis, targets preceded by AD speech elicited increased amplitude of the Negative central (Nc) component compared to targets preceded by ID speech, indicating increased attention. Experiment 2 (N = 23) explored whether ID versus AD speech influences attention allocation also without semantic content. The same targets were either preceded by human voice sounds without semantic content (“Uh-Ah”) following the prosody of either ID or AD speech register. No differences in attention allocation or object processing were observed. Experiment 3 (N = 18) contrasted ID speech with and without semantic content and found enhanced attention allocation following stimuli without semantic content, but increased object processing following stimuli with semantic content. Overall, the effects observed here are consistent with the idea that less familiar speech stimuli increase attention for subsequent objects. Semantic content of stimuli increased the depth of object processing in 7-month-olds.